What are the critical barriers to the development of hydrogen refueling stations in China? A modified fuzzy DEMATEL approach - Xu, Chuanbo; Wu, Yunna; Dai, Shuyu (Energy policy, 2020)
Hydrogen fuel cell vehicle is one of the important modalities of the next generation of new energy vehicles. As the basic infrastructure of hydrogen fuel cell vehicles, hydrogen refueling stations (HRSs) have drawn attention from all social circles. However, hindered by various barriers, the development of HRSs is much slower than the Chinese government's expectation. Hence, this study aims to explore critical barriers of the HRS development in China based on a modified fuzzy decision-making trial and evaluation laboratory (DEMATEL) method. Firstly, a barrier list is identified through a literature survey and expert consultation, which consists of four categories (economic, technological, social and political-regulatory aspect) and 12 potential barriers. Later, considering the subjectivity of threshold setting in the traditional fuzzy DEMATEL method, the K-means clustering algorithm is utilized to optimize the threshold value, and thus a modified fuzzy DEMATEL approach is proposed to investigate the prominence of these barriers and the cause-effect relationships among them. The results show that six barriers are regarded as key barriers to China's HRS development, and corresponding policy measures are formulated to mitigate or eliminate these critical barriers. •Barriers to the development of hydrogen refueling station in China are summarized.•The prioritization and influence severity of each barrier are obtained by a modified fuzzy DEMATEL.•Six barriers are regarded as key barriers hindering the hydrogen refueling station development.•Policy measures are formulated to mitigate or eliminate these critical barriers.